Pontos críticos para o desempenho dos voluntários na operacionalização de megaeventos esportivos - Abreu, Fabio Lanzillotta de (2015)
The purpose of the presentation is to analyze the main issues in the operationalization of a sports mega-event when thousands of volunteers become the work force without receiving any kind of remuneration, as Brazil will host, during the decade, important mega-events of that kind and will be in need voluntary workforce. For that reason, an explorative qualitative research was conducted, by means of individual interviews with volunteers having previous experience in sports events and with managers of the Rio de Janeiro 2016 Olympic and Paralympic Organizing Committee, in order to take a closer look at the analysis on incentives, event planning, organization during the event and the legacy in the vision of these two groups.